Sympathetic denervation facilitates L-type Ca2+ channel activation in renal but not in mesenteric resistance arteries. Issue 4 (April 2016) - Heumann, Philipp; Koenen, Anna; Zavaritskaya, Olga; Schütze, Konrad; Ramm, André; Schlüter, Torsten; Steinbach, Antje; Rettig, Rainer; Schubert, Rudolf; Grisk, Olaf
Abstract : Objectives: Sympathetic denervation enhances agonist-induced vasoconstriction. This effect may involve altered function of signaling mechanisms such as Rho kinase (Rock) and L-type Ca 2+ channels downstream from vasoconstrictor receptors. We tested if enhanced Rock and L-type calcium channel activation contribute to exaggerated norepinephrine-induced vasoconstrictions in renal and mesenteric resistance arteries after sympathectomy. Methods: Rats underwent neonatal sympathectomy or sham sympathectomy. Resistance arteries were investigated by small vessel myography. Vascular Rock and L-type Ca 2+ channel expression as well as Rock activation were investigated by quantitative real-time PCR and Western blot. Vascular smooth muscle cell (VSMC) membrane potential was recorded with microelectrodes. Results: Sympathetic denervation enhanced norepinephrine sensitivity in renal and mesenteric arteries. Both, Rock inhibition or L-type Ca 2+ inhibition shifted the norepinephrine concentration–response curve to the right. This effect was more pronounced in renal than in mesenteric arteries from sympathectomized vs. sham-sympathectomized animals. The L-type Ca 2+ channel activator S-(-)-BayK8644 elicited strong vasoconstrictions only in renal arteries from sympathectomized rats. Rock activity and L-type Ca 2+ channel α-subunit expression were similar in renal arteries from sympathectomized and sham-sympathectomized animals. VSMC membrane potential was −57.5 ± 2.0 and −64.3 ± 0.3 mV ( P < 0.01), respectively, in renal arteries from sympathectomized and from sham-sympathectomized rats. Depolarization enhanced and KATP channel activation abolished S-(-)-BayK8644-induced contractions in renal arteries from sympathectomized rats. Conclusion: Sympathetic denervation enhances L-type Ca 2+ channel-dependent signaling in renal but not in mesenteric arteries. This effect may be partly explained by the decreased VSMC membrane potential in denervated renal arteries. Abstract : Supplemental Digital Content is available in the text